Solid-State and Theoretical Investigations of Some Banister-Type Macrocycles with 2,2’-Aldoxime-1,1’-Biphenyl Units - Stroia, Ioan; Moraru, Ionuţ -Tudor; Miclăuş, Maria; Grosu, Ion; Lar, Claudia; Grosu, Ioana Georgeta; Terec, Anamaria (Frontiers in Chemistry, 2021)
In the context of helical chirality, bridging of biphenyl units leads to banister-type compounds and the stability of the resulted atropisomers may increase dramatically if suitable changes are performed in the linker unit that coils around the biphenyl moiety. A rigorous density functional theory (DFT) study was conducted for macrocycles containing rigid oxime ether segments connected to the biphenyl backbone in order to determine how the rotation barriers are influenced by the presence of either a flexible oligoethyleneoxide or a more rigid m-xylylene component in the macrocycle. The calculated values for the racemization barrier were in good agreement with those obtained experimentally and confirm the benefit of introducing a more rigid unit in the macrocycle on the stability of atropisomers. Solid-state data were obtained and computed data were used to assess the contribution brought by supramolecular associations observed in the lattice to the stabilization of the crystal structure. Beside introducing rigidity in the linker, complexation of flexible macrocycles with alkali metal ions is also contributing to the stability of atropisomers, leading to values for the racemization barrier matching that of the rigid macrocycle. Using diethylammonium cation as guest for the macrocycle, a spectacular increase in the barrier to rotation was observed for the resulted pseudo[2]rotaxane.